2007
DOI: 10.1681/asn.2006060634
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Ligation on Intrinsic Renal Cells Contributes to the Induction of Antibody-Mediated Glomerulonephritis via CXCL1 and CXCL2

Abstract: Autoimmune diseases such as glomerulonephritis are exacerbated by infection. This study examined the effect of the Toll-like receptor 4 (TLR4) ligand lipid A on the development of heterologous nephrotoxic nephritis. Administration of nephrotoxic antibody resulted in significant glomerular neutrophil infiltration and albuminuria only when a TLR4 ligand was administered simultaneously. The contribution of TLR4 on renal cells and circulating leukocytes was assessed. Bone marrow chimeras were constructed with TLR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 33 publications
5
86
1
Order By: Relevance
“…It exacerbates the neutrophil influx and proteinuria induced by passively administered glomerular-binding antibody. 11,12 The current study differs from our previous reports because, unlike heterologous nephrotoxic nephritis, the autologous phase is a model in which progressive disease occurs, and histological features closely resemble those seen in human glomerulonephritis.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It exacerbates the neutrophil influx and proteinuria induced by passively administered glomerular-binding antibody. 11,12 The current study differs from our previous reports because, unlike heterologous nephrotoxic nephritis, the autologous phase is a model in which progressive disease occurs, and histological features closely resemble those seen in human glomerulonephritis.…”
Section: Discussioncontrasting
confidence: 55%
“…We have recently established that stimulation of TLR2 and TLR4 can trigger disease in the heterologous phase of nephrotoxic nephritis. 11,12 This is a model of neutrophil-mediated acute glomerular inflammation induced by passively administered glomerular binding antibody. 13 For both TLR2 and TLR4, we demonstrated that stimulation of renal cell TLRs played an important role.…”
mentioning
confidence: 99%
“…TLR4 signalling also plays an important role in the development of various kidney diseases, yet the role of TLR4 in diabetic glomerulopathy or hyperlipidaemiainduced kidney damage remains to be elucidated [8][9][10][11][12][13]. Recently, Burkhardt et al and Bouma et al reported that serum S100A8/A9 complex concentrations were elevated in patients with diabetes [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis of S100A8 protein production in diabetic mice is currently under way in our laboratory. Candidate Tlr4-expressing cells in the diabetic kidney include macrophages, podocytes and mesangial and tubular epithelial cells [8,9]. So far, we have been unable to obtain reliable findings by immunohistochemistry using commercially available antibodies for TLR4, and we are now trying other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation